2010
DOI: 10.1051/0004-6361/201015030
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric radio structure and record jet of giant quasar 4C 34.47

Abstract: Context. Unification models for active galactic nuclei, AGN, predict that all quasars (radio sources associated with quasi-stellar objects) should be at a substantial angle with the sky plane. Aims. We test the predictions of the orientation unification model with the morphological and polarization properties of a giant quasar. Methods. The giant double-lobed radio source 4C 34.47, which is associated with quasi-stellar object B1721+343, is mapped at arcsecond scale resolution, and the data are subsequently an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Similarly, another source showed a symmetrical, faint emission on a different axis with respect to the jet one, consistent with relic lobes from a previous radio phase or jet precession (J1153.9+5848). Finally, for 4C +34.47, already showing two radio phases from our previous studies, we could confirm a discontinuous, knotty jet at a frequency an order of magnitude lower than the previous study from Hocuk & Barthel (2010). This is suggestive of either an intermittent radio activity, or of a plasma recollimation/expansion along the jet.…”
Section: S U M M a Ry A N D C O N C L U S I O N Ssupporting
confidence: 67%
See 1 more Smart Citation
“…Similarly, another source showed a symmetrical, faint emission on a different axis with respect to the jet one, consistent with relic lobes from a previous radio phase or jet precession (J1153.9+5848). Finally, for 4C +34.47, already showing two radio phases from our previous studies, we could confirm a discontinuous, knotty jet at a frequency an order of magnitude lower than the previous study from Hocuk & Barthel (2010). This is suggestive of either an intermittent radio activity, or of a plasma recollimation/expansion along the jet.…”
Section: S U M M a Ry A N D C O N C L U S I O N Ssupporting
confidence: 67%
“…These properties were not revealed at the lower resolution of the TGSS image discussed in Bruni et al (2020). Hocuk & Barthel (2010) first revealed the knotty structure of the southern jet from VLA observations at 1.4 GHz and 5 GHz, and also provided an estimate of the jet angle to line of sight. On the basis of the jet/counter-jet flux density ratio, and the jet bulk velocity, they infer a jet axis angle within 57 • from the line of sight.…”
Section: C +3447mentioning
confidence: 98%
“…A2, top-right panel). Hocuk & Barthel (2010), through detailed VLA observations, detected a one-sided jet in the inner kpc, analogously to 4C +63.22. An estimate of the viewing angle from the jet/counterjet emission ratio and kinematic arguments led to values <30°.…”
Section: Images From Surveys and The Literaturementioning
confidence: 86%
“…The optical clas-sification of this source's core supports a line of sight close to the jet axis (Seyfert 1). Also for this source, an estimate of the lobe magnetic field as reported by Ishwara-Chandra & Saikia (1999) allows a rough estimate of the Mpc lobe radiative age as done for the case of IGR J14488-4008 and B3 0309+411B: in this case we also assume a spectral break above 1 GHz as suggested by the steep spectral index measured by Hocuk & Barthel (2010). The estimated age is below 11 Myr, again at odds with the finding of Bruni et al (2019) who reported a GPS core in this source, and suggested a recent reactivation of the jet.…”
Section: Images From Surveys and The Literaturementioning
confidence: 99%
“…Results usually rely on indirect methods and are therefore often debated. The regions near AGN are also generally obscured (Spoon et al 2007;Hocuk & Barthel 2010). Predictions based on models and numerical simulations can aid observations to further our understanding of star formation.…”
Section: Introductionmentioning
confidence: 99%